Design Of Vertical Wind Turbine Power Plants For Light Trap In Onion Farming Lands - Shidiq, Muhammad Agus; Mustaqim, Mustaqim; Wibowo, Hadi; Farid, Ahmad; Rusnoto, Rusnoto (Mestro: Jurnal Teknik Mesin dan Elektro, 2024)
Trap lights, also known as insect traps, are used to attract light-loving insects when night falls. This device can also be used to count the population and presence of insects in agricultural land. From the beginning of planting, the use of light traps will help farmers detect pests. It seems that Indonesian society is still underutilizing wind energy as a source of electricity. One of the reasons is the low average wind speed in Indonesia. It is difficult to generate large amounts of electrical energy because wind speeds range from 3 m/s to 5 m/s. This research focuses on innovating existing tools by providing variations in wind speed and load on turbines, which are then compared to each other to produce turbine efficiency values. Therefore, an experimental method was chosen for this data collection. The test results show that the generator produces the highest power of 4.9833 Watts at a wind speed of 8.75 m/s and a power load of 7 Watts. On the other hand, the turbine achieves the highest efficiency value of 6.52% at a wind speed of 6.91 m/s and a power load of 7 Watts.